QUALITY OF SERVICE IN IMPLEMENTING THE COMPLETE SYSTEMATIC LAND REGISTRATION (PTSL) PROGRAM IN MAKASSAR CITY - Wahyuni, Sri; Guntur, Muhammad; Darwis, Muh; Aina, Asri Nur (Universitas Negeri Makassar, 2025)
This study aims to determine the quality of services for making complete systematic land certificates (PTSL) at the land office of the city of Makassar. To achieve this goal, the researcher used a qualitative descriptive research type. The data sources are primary data and secondary data. Data collection techniques using the method of observation, interviews and documentation. The data analysis technique used in this study is the Milles and Huberman model. The data validation used is source triangulation. Referring to the research objectives, the researcher uses the Zeithmal- Parasutaman-Berry service quality theory, which is used to assess the service of making land certificates using the PTSL program at the Makassar City Land Office. The results showed that the quality of service in making land certificates using the PTSL program at the land office of the city of Makassar, seen from 5 indicators, was said to be good or satisfactory. old and unstructured queuing system.